Urgensi Pemikiran Filsafat dalam Meningkatkan Mutu Pendidikan Matematika - Muthma'innah, M (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
Until now, philosophical thinking in the world of education, especially in learning mathematics is still far from expectations, because there are still many teachers who find it difficult to philosophize when learning mathematics. The purpose of this paper is to describe the urgency of philosophical thought in improving the quality of mathematics education. This research includes library research, using descriptive analysis techniques. The data collection technique uses documentation techniques by collecting the latest nationally indexed journal articles related to the urgency of philosophical thought in improving the quality of mathematics education.  The research results show that philosophical thinking is very urgent in improving the quality of mathematics education, because philosophical thinking was born from a teacher or educational observer who is critical in improving the quality and quality of mathematics education. This can be seen when teachers carry out research in improving the quality of learning mathematics in class. As for education observers, they will use their philosophical thinking in improving the quality of mathematics education through learning methods and models that are in accordance with the curriculum of mathematics education and learning.  The impact of this research in the future for teachers and education observers is to continue to think and philosophize in improving the quality of mathematics education, in solving mathematical problems that arise in the world of education, so that the quality of mathematics education in learning is improved and more enjoyable.  Hingga saat ini, pemikiran filsafat di dunia pendidikan khususnya dalam pembelajaran matematika masih jauh dari harapan, karena masih banyak guru yang merasa kesulitan dalam berfilsafat saat pembelajaran matematika. Adapun tujuan tulisan ini yaitu untuk mendeskripsikan urgensi pemikiran filsafat dalam meningkatkan mutu pendidikan matematika. Penelitian ini termasuk penelitian library research, dengan menggunakan teknik analisis deskriptif. Adapun teknik pengumpulan datanya menggunakan teknik dokumentasi dengan mengumpulkan artikel jurnal terupdate yang terindeks nasional berkaitan urgensi pemikiran filsafat dalam meningkatkan mutu pedidikan matematika. Hasil penelitian diperoleh pemikiran filsafat sangat urgen dalam meningkatkan mutu pendidikan matematika, karena pemikiran filsafat lahir dari seorang guru maupun pemerhati pendidikan yang kritis dalam memperbaiki kualitas dan mutu pendidikan matematika. Hal ini terlihat saat guru melaksanakan penelitian dalam memperbaiki kualitas pembelajaran matematika di kelas. Adapun bagi pemerhati pendidikan akan menggunakan pemikiran filsafatnya dalam memperbaiki mutu pendidikan matematika melalui metode dan model pembelajaran yang sesuai dengan kurikulum pendidikan dan pembelajaran matematika. Dampak bagi penelitian ini ke depannya untuk guru dan pemerhati pendidikan yaitu agar terus berpikir dan berfilsafat dalam mmeningkatkan mutu pendidikan matematika, dalam memecahkan permasalahan matematika yang timbul di dunia pendidikan, sehingga mutu pendidikan matematika dalam pembelajaran lebih meningkat dan menyenangkan.